Upaya Meningkatkan Kemampuan Membaca Al Quran Siswa SMK Maarif 2 Gombong Melalui Metode Tartil - Cahyani, Arsela Titin; Arwani, Aziz; Fatimah, Siti (Tarbi: Jurnal Ilmiah Mahasiswa, 2024)
The ability to read the Koran is very important, because reading the Koran is a manifestation of one's faith in Allah. The Tartil method is one of the methods designed and written by Gazali in early 1993 to help students learn more quickly and practically. Reciting Al-Qur'an. This study aims to determine the success of the tartil method in improving the ability to read the Koran for students at SMK Ma'arif 2 Gombong. This study was carried out using a qualitative approach and the Classroom Action Research (CAR) method through two cycle phases. The subjects in this study were the 10th grade students of TPTU 1, totaling 42 students consisting of male students. 2. Improving the Reading Ability of the Students of Maarif 2 Gombong Vocational School with the Tartil Method seen from the students' scores in each cycle. In cycle 1 30 students (65%), and in cycle 2 it increases to 43 students at 93%. This proves that the students' ability to read the Koran at Maarif 2 Gombong Vocational School with the Tartil Method has significantly increased